Platform capitalism: challenges for the labour market in modern Russia - Ketov, Alexander R. (Journal of the Belarusian State University. Sociology, 2023)
The article discusses the changes in the labour market in modern Russia associated with the advent of a new economic model – the so-called platform capitalism. Thanks to scientific and technological progress, social networks, search engines, applications can freely collect user data, process it and use it on advertising platforms. Platform companies are becoming an environment in which economic interaction takes place, allowing them to extract maximum benefits, they react faster than their competitors to changes in the market situation. Platform companies have created and are developing their own ideology, according to which they are a space in which equal use of resources, cooperation, cooperation is possible. These relations are defined by them as sharing economy. In fact, platform companies contribute to the strengthening of negative trends in the labour market, reducing the rights of workers. There is a massive precarisation of labour, a transition from labour relations guaranteed by labour legislation to unreliable, non-traditional employment, which does not imply any social and labour rights and guarantees. The declared freedom is actually an illusion, which platform companies promote under the guise of an outwardly attractive sharing economy, turns into precarisation of labour, lack of social guarantees, constant processing within the framework of an equal partnership between employees and platforms.